Decavanadate in vitro and in vivo effects: facts and opinions - Aureliano, M. (2014)
This review covers recent advances in the understanding of the in vitro and in vivo effects of decavanadate, (V10O28)6 −, particularly in mitochondria. In vivo toxicological studies involving vanadium rarely account for the fact that under physiological conditions some vanadium may be present in the form of the decavanadate ion, which may behave differently from ortho- and metavanadates. It has for example been demonstrated that vanadium levels in heart or liver mitochondria are increased upon decavanadate exposure. Additionally, in vitro studies have shown that mitochondrial depolarization (IC50, 40 nM) and oxygen consumption (IC50, 99 nM) are strongly affected by decavanadate, which causes reduction of cytochrome b (complex III). We review these recent findings which together suggest that the observed cellular targets, metabolic pathway and toxicological effects differ according to the species of vanadium present. Finally, the toxicological effects of decavanadate depend on several factors such as the mode of administration, exposure time and type of tissue.